The Effect of Hybrid Training Combined with On demand Classes - Kunieda, Yoshiaki; Niwa, Shojiro; Dee, Sann; Kashima, Hideyuki; Murai, Koji (Advances in Social Sciences Research Journal, 2021)
One aspect of life hit hard by the COVD-19 pandemic in 2020 was education in general and, in this case, actual ship training. The same is true for anchoring training, implemented annually as part of maritime training. Therefore, to conduct ship training effectively and briefly, this study advocates hybrid training, that is, shortened practical training combined with on demand video learning materials created and distributed to students in advance. Group work on ship handling planning that lasts for three to six hours is normally conducted annually in traditional classes. However, because of the pandemic, the allotted time for group work was reduced to approximately 1.5 hours. Therefore, in 2020, we conducted hybrid training, that is, anchoring training that included on demand video learning materials. Compared to students’ 66.3% average achievement rate in 2018 and 2019, the average in 2020 was 78.3%. ‘Anchoring procedure’ and ‘altering course’ items showed a particularly large gap in evaluation. The following were effects of hybrid training: (1) Videos that can be watched in advance can also be viewed repeatedly at one’s own pace. (2) The capacity to watch videos via smart phones provides students with better access. (3) As videos can be watched in advance, students become familiar with concepts before training, thus leading to better understanding of the training’s content and purpose. These results demonstrated hybrid training’s effect when practical training is combined with on demand materials.